Imaging Features of Prostate Sarcoma: A Case Report - Federica Masino; Laura Eusebi; Manuela Montatore; Giuseppe Maria Andrea D’Arma; Giuseppe Sortino; Lucia Pitoni; Alessandra Filosa; Giuseppe Guglielmi (Prague Medical Report, 2025)
A 54-year-old man presented to our clinic complaining of painful ejaculation. The patient underwent various imaging modalities, including ultrasound, transrectal ultrasound, prostate magnetic resonance imaging and positron emission tomography/computed tomography that detected a voluminous mass originating from the prostate. Histological examination diagnosed a prostate sarcoma, a rare mesenchymal tumour. This case offers an opportunity to evaluate a rare subtype of prostate cancer and to describe its main imaging features with an educational approach.